IMPROVING STUDENT SOCIAL INTERACTION ABILITY USING PROBLEM BASED LEARNING (PBL) METHODS IN AQIDAH AHLAK COURSES AT MIN 10 BOYOLALI ACADEMIC YEAR 2022/2023 - Khoirudin, K; Subando, Joko; Fatimah, Meti (Proceeding of International Conference of Islamic Education, 2023)
This study aims to find out that the Problem Basic Learning (PBL) method in the Aqeedah Akhlak subject can improve the social interaction abilities of students at MIN 10 Boyolali in the 2022/2023 academic year. This research is a type of classroom action research. This research was conducted from April to June 2023. The subjects of this study were students of Class IV MIN 10 Boyolali with a population of 53 students, so all were taken. Data is taken through documents and questionnaire scores, with the T-Test test. The PBL method can increase students' social interaction skills by 22% starting from pre-action, then continuing in cycle I to increase to 70.4% and in cycle II to increase again to 96.3%. The use of the PBL method is applied to students of class IV MIN 10 Boyolali in the Aqidah Akhlak subject so that students can more easily and quickly improve their social interaction skills.